ATCA 3 mm observations of NGC 6334I and I(N): dense cores, outflows, and an UCH II region - Beuther, H.; Walsh, Andrew; Thorwirth, S.; Zhang, Q.; Hunter, R.; Megeath, S.; Menten, K. (EDP Sciences, 2008)
Aims:We investigate the dense gas, the outflows, and the continuum emission from the massive twin cores NGC 6334I and I(N) at high spatial resolution.Methods: We imaged the region with the Australia Telescope Compact Array (ATCA) at 3.4 mm wavelength in continuum, as well as CH3CN(5_K{-}4_K) and HCN(1-0) spectral line emission.Results: While the continuum emission in NGC 6334I mainly traces the UCHii region, toward NGC 6334I(N) we detect continuum emission from four of the previously identified dust continuum condensations that are of protostellar or pre-stellar nature. The CH3CN(5_K{-}4_K) lines are detected in all K-components up to energies of 128 K aboveground toward two protostellar condensations in both regions. We find line width increasing with increasing K for all sources, which indicates a higher degree of internal motions of the hotter gas probed by these high K-transitions. Toward the main mm and CH3CN source in NGC 6334I, we identify a velocity gradient approximately perpendicular to the large-scale molecular outflow. This may be interpreted as a signature of an accretion disk, although other scenarios, e.g., an unresolved double source, could produce a similar signature. No comparable signature is found toward any of the other sources. HCN does not trace the dense gas well in this region but it is dominated by the molecular outflows. While the outflow in NGC 6334I exhibits a normal Hubble-law like velocity structure, the data are consistent with a precessing outflow close to the plane of the sky for NGC 6334I(N). Furthermore, we observe a wide ( 15.4 km s-1) HCN absorption line,much broader than the previously observed CH3OH and NH3 absorption lines.